Adverse surroundings and their health impact during university education of singers - Monteiro de Castro dos Santos Braga, Leila Claudia (2021)
This study derives from a master’s thesis that aimed to examine the promotion of health in singing college students in two public universities in Rio de Janeiro. During the field research, the surroundings to which the singers were exposed to were one of the most relevant aspects amongst the observed, becoming the goal of this article. The instruments used in this field study were participant observation and interviews. The analysis of the transcripts of the oral records was conducted through thematic coding using the method of Grounded Theory and triangulated with the data collected by observation. It was concluded that a bad education environment could be associated with possible damages to the respiratory, vocal, mental and hearing health of this group, and it may still influence the singer’s artistic performance.